Omentel transplantation for primary occipital neuralgia - Rafael, Hernando (2009)
Introduction. Occipital neuralgia is a common cause of headache, it may be primary or secondary, and the goal of therapy is to alleviate pain.Case report. A 51-year-old man was admitted with a 6-week history of primary occipital neuralgia. Pain began at the left lateral area of the neck and sometimes it took the right side. The patient had been a smoker since he was 15 years old. When he was 30, 40, and 45 years old, he had three episodes of left occipital neuralgia, and their average duration was 4 months in each time. Neurological examination was normal. A CT scan showed atherosclerosis in the V4 segment of the left vertebral artery. An omental transplantation upon the upper cervical cord and the dorsal and caudal surface of the medulla oblongata was performed. The patient experienced complete relief of his pain since the very first day after the procedure.Conclusion. Nowadays, two years after surgery, the patient has no primary occipital neuralgia. This result suggests that ischemic neurons in the caudal portions of subnucleus caudalis are responsible for primary occipital neuralgia.